ELASTO-PLASTIC STRESS ANALYSIS OF COMPOSITE PLATES WITH QUADRILATERAL HOLES - Muzaffer TOPCU; Ayşe ÖNDÜRÜCÜ (Pamukkale University Journal of Engineering Sciences, 2000)
In this study, elasto-plastic stress analysis have been made for composite plates containing a central hole subjected to uniaxial tension under various uniformly distributed loads. In the solution, ısoparametric quadrilateral elements with nine nodes have been used. For different geometries of the holes and 0 and 90 degrees reinforcement angles, residual stress variations have been investigated.